A large‐scale gene discovery for the red palm weevil Rhynchophorus ferrugineus (Coleoptera: Curculionidae). (14th January 2013) - Wang, Lei; Zhang, Xiao‐Wei; Pan, Lin‐Lin; Liu, Wan‐Fei; Wang, Da‐Peng; Zhang, Guang‐Yu; Yin, Yu‐Xin; Yin, An; Jia, Shan‐Gang; Yu, Xiao‐Guang; Sun, Gao‐Yuan; Hu, Song‐Nian; et al.
Abstract The red palm weevil (RPW; Rhynchophorus ferrugineus) is a devastating pest of palms, prevalent in the Middle East as well as many other regions of the world. Here, we report a large‐scale de novo complementary DNA (cDNA) sequencing effort that acquired ∼5 million reads and assembled them into 26 765 contigs from 12 libraries made from samples of different RPW developmental stages based on the Roche/454 GS FLX platform. We annotated these contigs based on the publically available known insect genes and the Tribolium castaneum genome assembly. We find that over 80% of coding sequences (CDS) from the RPW contigs have high‐identity homologs to known proteins with complete CDS. Gene expression analysis shows that the pupa and larval stages have the highest and lowest expression levels, respectively. In addition, we also identified more than 60 000 single nucleotide polymorphisms and 1 200 simple sequence repeat markers. This study provides the first large‐scale cDNA dataset for RPW, a much‐needed resource for future molecular studies.